Pintura y escultura digital 3d con ZBrush aplicada a la Arqueología - Marta Ángeles Estalayo Moreno (Virtual Archaeology Review, 2011)
The technology 3D is every day developing by leaps and bounds. Programs like 3D Studio Max, Lightwave, Maya, ZBrush … allow to model in 3D with constant innovations in its palettes of tools and its render systems and resolution. Using a technology which generally is applied for computer graphics, games, advertising or films, archaeologists reconstruct the past to do it graphically closer, more understandable to all citizens.